G453 High flow nasal prong therapy for infants <24 months of age with bronchiolitis:experiences from a tertiary paediatric intensive care unit. (7th April 2014) - Gangadhara, M; Ali, T
Abstract : Aims: To describe the practice of high flow nasal prong (HFNP) therapy in infants <24 months of age with bronchiolitis. To identify the patient subgroups on HFNP requiring escalation of therapy to either other non-invasive or invasive ventilation. To identify any adverse events associated with HFNP therapy. Methods: Retrospective chart review from the local database (Carevue) of infants <24 months of age admitted to PICU with bronchiolitis between April 2011 and March 2012 for HFNP therapy. Length of stay (LOS), ventilatory requirements and risk factors were analysed. Results: Total of 74 patients received HFNP therapy during this period. Out of these, 26 (35%) patients were infants <24 months of age with bronchiolitis. Median age and LOS was 2.75 months and 6 days respectively. 7 infants (27%) were ex-preterms with chronic lung disease and 3 infants (11.5%) had congenital heart disease. 21 (80%) infants were RSV positive. A total of 10 (38%) infants were intubated directly and 16 (62%) infants had a trial of HFNP therapy. Overall, 3 (19%) infants needed escalation to mechanical ventilation. 13 (50%) infants received only HFNP therapy as respiratory support for bronchiolitis. All 26 infants were eventually discharged from the unit. No adverse events were identified with the use of HFNP therapy. Conclusion: HFNP therapy was successful in the vast majority of patients, particularly in those without risk factors. HFNP therapy has changed ventilatory practice in infants <24 months of age in our institution, and appears to reduce the need for intubation in infants with bronchiolitis.